Forecasting the maximum absorption of bacteriochlorofyll a derivatives subject to conformational flexibility of molecules. - A. A. Mezentseva; N. A. Mironova; E. V. Burlyeva (Тонкие химические технологии, 2008)
The relationship "structure – property" of the bacteriochlorofyll a derivatives has been investigated. The prognostic procedure of thermodynamic and spectral characteristics for group of these compounds has been offered.